Echocardiogram : left ventricle chamber detection using image processing - Thoiebah, Ahmad Mukhtar (2012)
The left ventricle is one of the four chambers in the human heart. It receives oxygenated blood from the left atrium through the mitral valve and pumped into the aorta through the aorta valve. Heart valve failure could affect the productivity of the delivery of blood to other parts of the human body. The effect of this failure will lead to death. Echocardiogram is a diagnostic test to detect heart diseases. This study is based on the echocardiogram video taken from the Hospital Universiti Kebangsaan Malaysia (HUKM). This video is a video taken of patients left ventricle valves. The study was done with the video processing to generation of static images. From the static image, the image has been carried out to obtain the size of the left ventricle of the heart. The objective of this study was to detect the properties of cardiac chamber echocardiogram images taken from patients. In this study, an analysis of the size of the heart valves has been committed. Image processing techniques used to detect the size or diameter of the left ventricular chamber. Results are expected is to develop a graphical user interface (GUI) with the ability to import and display parameters echocardiogram images using MA TLAB simulation.